Programme for the establishment of a high-performance info-communications infrastructure in Japan. - YOSHIBA, Noboru (1995)
Presents a summary of a report which explained the significance of an info-communications infrastructure in building the intellectually creative society of the twenty-first century. Describes follow-up policy measures that are being taken by the government of Japan.